Google's role in digital ad intermediation : An overview of leveraging practices and related competition concerns - Witte, Alexander (My University, 2020)
The market for digital advertising is proliferating with global turnover figures of $333 billion in 2019, more than half of the total ad spend worldwide (Enberg, 2019). Most of the advertisers’ money is spent on so-called ‘walled gardens’, i.e., data-rich platforms like Google, Facebook, or Amazon (Adshead, Forsyth, Wood, & Wilkinson, 2019). Google was the largest seller of online advertisements in 2019, with net digital ad revenues of $103.7 billion, roughly one-third of global digital ad spending in 2019. For comparison, the second-largest ad seller, Facebook, totaled $67.37 billion in ad revenue. In 2018, less than 20% of total digital ad expenditures were spent on the open web (JounceMedia, 2018), i.e., the myriad of publishers of online content, ranging from large news publishers to small online blogs. These publishers rely on digital advertising revenue to fund their business, even more so since ad revenues from print media have steadily been declining (Cairncross, 2019). To facilitate the trading of ads and inventory between publishers and advertisers, intermediary service providers, the so-called “ad tech stack” emerged (CMA, 2020a). However, publishers have expressed concerns that these intermediary service providers, with Google being the largest provider, accrue an excessive amount of advertisers’ money and thereby deprive publishers of vital revenue (Cairncross, 2019; Furman, Coyle, Fletcher, McAuley, & Marsden, 2019). Recent empirical investigations, e.g., from the U.K. Competition and Market Authority (CMA) or the Incorporated Society of British Advertisers (ISBA), found that about one-third (CMA, 2020e) to one-half (ISBA, 2020) of advertisers’ money is accrued by the various intermediaries. Industry stakeholders relate the excessive fees to a lack of competition in the market (CMA, 2020a). In particular, Google is accused of engaging in practices that distort competition to the detriment of publishers and competitors in ad tech (Geradin & Katsifis, 2019a). The concerns expressed by industry stakeholders have increasingly drawn regulatory interest. For example, the CMA (2020a) published a study on online platforms and digital advertising in July 2020. Also, the French Competition Authority (FCA, 2018) and the German Bundeskartellamt (2018) are or have investigated the online advertising sector. Similarly, in the U.S., Attorney Generals of 50 U.S. states announced antitrust investigations of Google’s role in online advertising (Romm, 2019). Concurrently, Google switched to a first-price unified auction by the end of 2019, claiming the transition is motivated by the desire to create a more fair and transparent market for everyone (Bigler, 2019), thereby soliciting perceptions of possible self-regulation (Geradin & Katsifis, 2020). Related to the concerns expressed by industry stakeholders and the increasing regulatory interest, this thesis seeks to examine Google’s role in online ad intermediation. Given its importance for the sustainability of the provision of free online content, healthy competition in these markets is of vital importance to society. Specifically, the thesis is concerned with examining possible anti-competitive practices by Google and whether Google’s recently deployed changes to the industry are genuinely motivated by increasing the benefits for the open display advertising industry as a whole.